Perbedaan Penggunaan Valve Racing Carbon Fiber Dan Standar Terhadap Daya Mesin Motor 2 Langkah 150 Cc Dengan Bahan Bakar Pertalite - Bramantyo Satrio Kinayungan Budi Wicaksono Ilyas; Khotibul Umam; Ardhi Harist Hirosana; Ivan Hardi Nurul Ikhsan; Trisma Jaya Saputra (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
On a 2-stroke motorcycle, this can be wasteful and one of the causes is the incomplete combustion process. In the fuel reporting system on a 2 stroke motorbike, it still uses a carburetor system and also uses a valve. The valve is used in learning the fuel and air mixture from the carburetor. Valve mechanism to regulate the amount of fuel and air mixture entering the combustion chamber. In addition, it also acts as a door to open and close the combustion chamber when flushing of the cylinder occurs. If the valve system is not optimal, a lot of the fuel and air mixture is wasted and the motorcycle engine does not work optimally. Because when suctioning the tongue, the valve must immediately open quickly and wide so that the fuel and air mixture that enters is maximized. Likewise, when exhausting, it must also close quickly so that the fuel and air mixture does not return to the carburetor. In writing this research, the data sources required consist of two data, namely 1. Secondary Data Secondary data is data obtained from other existing sources, including books, related journals, and websites. 2. Primary Data Primary data is data obtained from the results of testing the use of standard valves that are replaced with racing carbon fiber valves. Primary data obtained during the test includes the results of changes in power (Hp) and torque (Nm) obtained. Based on the data obtained from the results of the research that has been done, it shows that there is a difference in the power obtained on a motorbike using a standard valve with a motor using racing carbon fiber valves. Based on the graphic image above, the results of the study show that the power generated by the racing carbon fiber valve components has a slightly higher value when compared to those using standard valve components. The difference in power generated is due to the difference in the size of the valve produced by the valve used. . This is because the fuel and air mixture enters the cylinder chamber faster so that combustion becomes better by replacing the valve racing carbon faiber components.